Peningkatan Kualitas Produk Kopi Tora Cafe Chocolate Menggunakan Metode Six Sigma DMAIC Pada Perusahaan Makanan di Tangerang - Cipto Suparman (Universitas Tangerang Raya, 2026)
PT CCR is a major company in Tangerang Regency that produces various types of coffee beverages, including Tora Cafe Chocolate. However, the production process still encounters problems, particularly a high number of defective products on the packing line. to analyze this issue, this research applied the Define, Measure, Analyze, Improve, Control (DMAIC) method, which has been proven effective in reducing the Defects Per Million Opportunities (DPMO) rate and increasing the sigma level of a production process. Based on data from April to June 2025, three primary defects were identified in Tora Cafe Chocolate products: wrinkled packaging, leaking packaging, and improper packaging size referred. The most frequent defect was improper packaging size, accounting for approximately 34.82% of all defects. A root cause analysis was conducted using the 5W+1H framework, examining five key factors: machine, man, material, environment, and method. Prior to improvement, the DPMO value was recorded at 56,274, with a corresponding sigma level of 3.09. Improvement efforts included several initiatives, such as developing a training schedule for operators, performing machine maintenance and repair, creating a specialized control form for the packing machine, maintaining workplace cleanliness, enhancing quality supervision, and modifying equipment After implementing these improvements from July to September 2025, significant results were achieved. The sigma level increased to 3.68, while the DPMO value decreased to 15.146 per million production.